RESEARCH OF THE RELATION "URBAN AGRICULTURE - RURAL ECONOMY" - V. Blazheva (Trakia Journal of Sciences)
More and more companies are striving to provide fresh food production in the immediate vicinity of major cities, thus shortening the supply chain for the end user. According to FAO (Food and Agricultural Organisaton), about 800 million people worldwide cultivate different crops in and around cities, which means that 20% of the world's urban population is in one form or another occupied in urban agriculture (1). Rural areas make up half of Europe's territory and employ around 20% of the population. (2). Due to this reason, the attention is drawn to the contrast between the urban agriculture and the rural economy. The aim is to explore and reveal the "urban agriculture - rural economy" relation. The methods of the present study are scientific research methods: comparative analysis method, induction and deduction method, retrospective analysis and others; illustrative methods - tables, figures and others. In terms of expected outcomes, this article focuses on highlighting the social, economic and environmental aspects of the emergence of the correlation between urban agriculture and the rural economy. The final part focuses on the challenges of theurban agriculture and the rural economy.